Oblicz wartość liczbową wyrażeń:

a) 4a²-1-½(a-3)² dla a= -1
b)a(2-b)+b³+(a+b)² dla a= -2 b= -3
c)3(a²-b²)-4a-4b dla a= -0,5 b=0,1
d)2(a-b)²-3(a+b)(a-b) dla a= ⁵/₂ b= ³/₂
e)(a-1)(a-2)=(a-3)(a-4) dla a= -0,5
f)(2x+3y)²-2,5x²+3,5y² dla x= 2,5 y= -0,5

POTRZEBNE NA DZIŚ !

3

Odpowiedzi

2009-10-01T19:40:08+02:00
A) 4a²-1-½(a-3)² dla a= -1
4(-1)²-1-½(-1-3)² = 4*1-1-½*16=4-1-8=-5

b)a(2-b)+b³+(a+b)² dla a= -2 b= -3
-2(2+3)+(-3)³+(-2-3)² = -4-6-27+25=-12

c)3(a²-b²)-4a-4b dla a= -0,5 b=0,1
3(-0,5²-0,1²)-4*(-0,5)-4*(-0,5)-4*0,1 = 3(0,25+0,01)+2+2-0,4 = 0,75+0,03+2+2-0,4=4,38

d)2(a-b)²-3(a+b)(a-b) dla a= ⁵/₂ b= ³/₂
2(⁵/₂-³/2)²-3(⁵/₂+³/₂)(⁵/₂-³/₂) = 2-3*4*1=2-12=-10

e)(a-1)(a-2)=(a-3)(a-4) dla a= -0,5
(-0,5-1)(-0,5-2)=(-0,5-3)(-0,5-4)
-1,5*(-2,5)=-3,5*(-4,5)
3,75=15,75
3,75-15,75=-12

f)(2x+3y)²-2,5x²+3,5y² dla x= 2,5 y= -0,5
(2*2,5+3*-0,5)²-2,5*2,5²+3,5*(-0,5)² = (5-1,5)²-2,5*6,25+3,5*0,25 = 3,5²-15,625+0,875 = 12,25-15,625+0,875 = -2,5
2009-10-01T20:00:42+02:00
A) 4a²-1-½(a-3)² dla a= -1
4*(-1)²-1-½(-1-3)²=4-1-½(1+3+3+9)=
3-½(16)= 3-8= -5
b)a(2-b)+b³+(a+b)² dla a= -2 b= -3
-2(2-(-3)+-3³+(-2-3)²=
-10-27+25= -12
reszte zrob sam/a bo juz chyba rowumiesz? :)
Najlepsza Odpowiedź!
2009-10-01T20:02:04+02:00
A). 4a²-1-½(a-3)² dla a= -1
4(-1)²-1-½(-1-3)² = 4*1-1-½*16=4-1-8=-5
b). a(2-b)+b³+(a+b)² dla a= -2 b= -3
-2(2+3)+(-3)³+(-2-3)² = -4-6-27+25=-12
c). 3(a²-b²)-4a-4b dla a= -0,5 b=0,1
3(-0,5²-0,1²)-4*(-0,5)-4*(-0,5)-4*0,1 = 3(0,25+0,01)+2+2-0,4 = 0,75+0,03+2+2-0,4=4,38
d). 2(a-b)²-3(a+b)(a-b) dla a= ⁵/₂ b= ³/₂
2(⁵/₂-³/2)²-3(⁵/₂+³/₂)(⁵/₂-³/₂) = 2-3*4*1=2-12=-10
e). (a-1)(a-2)=(a-3)(a-4) dla a= -0,5
(-0,5-1)(-0,5-2)=(-0,5-3)(-0,5-4)
-1,5*(-2,5)=-3,5*(-4,5)
3,75=15,75
3,75-15,75=-12
f). (2x+3y)²-2,5x²+3,5y² dla x= 2,5 y= -0,5
(2*2,5+3*-0,5)²-2,5*2,5²+3,5*(-0,5)² = (5-1,5)²-2,5*6,25+3,5*0,25 = 3,5²-15,625+0,875 = 12,25-15,625+0,875 = -2,5